Preparation method of core-shell structure Ru / CeO2 (at) COF catalyst and application of core-shell structure Ru / CeO2 (at) COF catalyst in water electrolysis hydrogen evolution reaction
By coating COF on the surface of cerium oxide and loading Ru nanoparticles, the core-shell structure-type Ru/CeO2@COF catalyst was prepared, which solved the problem of poor activity of cerium oxide catalysts, and significantly improved the electrocatalytic activity and stability of the catalyst.
Patent Information
- Application Number
- CN202510090031.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-01-21
AI Technical Summary
The existing cerium oxide catalysts have poor activity in electrocatalytic hydrolysis reactions, mainly due to their small specific surface area, poor adsorption capacity, poor conductivity and stability.
Core-shell support material is constructed by coating covalent organic frame material (COF) on the surface of spherical cerium oxide, and loading elemental Ru nanoparticles by surface reduction method to prepare core-shell structural Ru/CeO2@COF catalyst.
The specific surface area of the cerium oxide surface is effectively increased, the adsorption capacity and conductivity of the catalyst are enhanced, thereby improving the electrocatalytic activity and stability of the catalyst.
Smart Images

Figure CN119913547A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of materials and electrocatalysis, and specifically relates to a method for preparing a core-shell structured Ru / CeO2@COF catalyst and application thereof in a hydrogen evolution reaction by electrolysis of water. Background Art
[0002] In recent years, the academic and industrial circles generally believe that hydrogen energy is a clean and green energy that can effectively replace fossil energy. It has many advantages such as wide sources, high combustion calorific value, clean and pollution-free, and multiple forms of utilization. It is the only new energy that meets the requirements of resources, environment, and sustainable development at the same time, and is the ultimate energy of the 21st century. Among the various industrial hydrogen production technologies currently available, water electrolysis is considered to be one of the most promising methods for large-scale production of hydrogen energy due to its simple process and high hydrogen production efficiency. In the hydrogen evolution reaction (HER), due to the high energy required for the process and the slow reaction kinetics, the hydrogen evolution efficiency is low. Therefore, screening high-performance catalysts can promote the adsorption of reaction intermediates and the desorption of products, reduce the activation energy in the reaction process, and thus improve the hydrogen evolution efficiency.
[0003] The spherical cerium oxide surface contains reversible Ce 3+ / Ce 4+ Redox pairs and tunable oxygen vacancies are considered to be a promising catalytic material. However, due to its weak adsorption effect on molecules, the contact between its surface active sites and substrates is limited, resulting in poor activity for catalyzing HER and failing to effectively promote HER. On the other hand, the poor conductivity of cerium oxide further limits its activity in the electrocatalytic HER reaction. Based on this, using surface modification methods to improve the adsorption capacity of the spherical cerium oxide surface and further using elemental metal nanoparticles to improve the conductivity of the catalyst, thereby improving the catalyst activity, is an effective way to modify cerium oxide-based catalysts for the electrocatalytic HER reaction. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a method for preparing a core-shell structured Ru / CeO2@COF catalyst in view of the deficiencies of the above-mentioned prior art. The method uses a surfactant as an inducing agent, and through a condensation reaction, a COF is coated on the surface of a spherical cerium oxide to construct a core-shell carrier material, and a single Ru nanoparticle is loaded through a surface reduction method to prepare a core-shell structured Ru / CeO2@COF catalyst, which effectively increases the specific surface area of the cerium oxide surface, enhances the adsorption capacity of the catalyst, and improves the conductivity of the catalyst, thereby improving the electrocatalytic activity and stability of the catalyst, and solves the problems of small specific surface area, poor adsorption capacity, poor conductivity and stability of the existing cerium oxide catalyst.
[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing a core-shell structure Ru / CeO2@COF catalyst, characterized in that the method comprises the following steps:
[0006] Step 1, ultrasonically dispersing spherical CeO2 particles in water, then slowly adding polyethyleneimine PEI aqueous solution and stirring at room temperature, and centrifugally washing to obtain PEI surface-treated CeO2 nanoparticles;
[0007] Step 2: Add the PEI surface-treated CeO2 nanoparticles obtained in step 1 to anhydrous acetonitrile containing PVP for ultrasonic dispersion, then add 2,5-dimethoxybenzene-1,4-dicarboxaldehyde DMTP and 1,3,5-tris(4-aminophenyl)benzene TAPB and stir, then add glacial acetic acid to react at room temperature, then add glacial acetic acid to heat and react, and obtain a core-shell CeO2@COF carrier material after centrifugation and washing;
[0008] Step 3: dissolve RuCl3 in methanol to prepare RuCl3 methanol solution, disperse the core-shell CeO2@COF carrier material obtained in step 2 in the methanol solution, then slowly drop the RuCl3 methanol solution and perform ultrasonic dispersion treatment, then slowly drop sodium borohydride aqueous solution for reduction, repeatedly wash, centrifuge and dry to obtain a core-shell structured Ru / CeO2@COF catalyst.
[0009] In view of the defects of small specific surface area, poor adsorption capacity, poor conductivity and stability of cerium oxide, the present invention uses PEI and PVP surfactants as inducing agents, utilizes Schiff base condensation reaction, makes covalent organic framework material (COF) grow on the surface of cerium oxide, and forms a shell coated on the surface of spherical cerium oxide, constructs core-shell CeO2@COF carrier material, and then based on this carrier, uses RuCl3 as a precursor, utilizes surface reduction method, and evenly loads elemental Ru nanoparticles on the surface of the carrier to obtain core-shell structure type Ru / CeO2@COF catalyst. By constructing a core-shell structure, on the one hand, the specific surface area of cerium oxide surface is increased, and the porous morphology of COF is utilized to enhance the adsorption capacity of the catalyst, thereby promoting the effective contact between the catalyst and the substrate, and on the other hand, effectively preventing the active sites from being covered by bubbles gathered on the surface, reducing the occurrence of agglomeration, increasing the stability of the catalyst, and enabling it to be quickly and repeatedly exposed to the surrounding electrolyte, thereby obtaining a rapid mass transfer capacity, which helps to improve the electrocatalytic activity of the catalyst.
[0010] The method for preparing the core-shell structure Ru / CeO2@COF catalyst is characterized in that the size of the spherical CeO2 particles in step 1 is 200nm to 300nm. By using spherical CeO2 particles with a small particle size and a large specific surface area, the contact area between the catalyst and the electrolyte is further increased, thereby improving the electrocatalytic activity of the catalyst.
[0011] The above-mentioned method for preparing a core-shell structure Ru / CeO2@COF catalyst is characterized in that the concentration of the spherical CeO2 particles ultrasonically dispersed in water in step one is 10 mg / mL to 40 mg / mL, the concentration of the polyethyleneimine PEI aqueous solution is 50 mg / mL to 200 mg / mL, and the mass ratio of polyethyleneimine PEI to spherical CeO2 particles is 3:1 to 6:1.
[0012] The above-mentioned method for preparing a core-shell structure Ru / CeO2@COF catalyst is characterized in that the ultrasonic dispersion time in step one is 1 hour, and the stirring time at room temperature is 1 hour to 2 hours; the ultrasonic dispersion time in step two is 0.5 hours to 2 hours; and the ultrasonic treatment time in step three is 1 hour to 2 hours.
[0013] The above-mentioned method for preparing a core-shell structure Ru / CeO2@COF catalyst is characterized in that the mass ratio of DMTP to TAPB in step 2 is 40-120:48-144, and the stirring time is 5 min to 20 min.
[0014] The method for preparing the core-shell structure Ru / CeO2@COF catalyst is characterized in that the reaction time at room temperature in step 2 is 4h to 6h, and the heating reaction temperature is 80°C and the time is 12h.
[0015] The above-mentioned method for preparing a core-shell structure Ru / CeO2@COF catalyst is characterized in that the 2,5-dimethoxybenzene-1,4-diformaldehyde DMTP and 1,3,5-tris(4-aminophenyl)benzene TAPB described in step 2 can also be replaced by metaphenylenediamine MPA and terephthalaldehyde TPA in a mass ratio of 60 to 240:72 to 244. The present invention adjusts the shell thickness of the core-shell structure by adjusting the addition amount of the ligands DMTP and TAPB; generally, other ligands with amino groups and aldehyde groups, such as MPA and TPA, can also be selected as organic ligand combinations for synthesizing COF materials.
[0016] The method for preparing the core-shell structure Ru / CeO2@COF catalyst is characterized in that the loading amount of Ru in the core-shell structure Ru / CeO2@COF catalyst in step 3 is 1% to 20% by mass.
[0017] At the same time, the present invention also discloses an application of a core-shell structured Ru / CeO2@COF catalyst prepared by the method described above in a hydrogen evolution reaction by electrolysis of water.
[0018] Compared with the prior art, the present invention has the following advantages:
[0019] 1. The present invention constructs a core-shell CeO2@COF carrier material by coating COF on the surface of spherical cerium oxide, and loads elemental Ru nanoparticles to prepare a core-shell structured Ru / CeO2@COF catalyst, which effectively increases the specific surface area of the cerium oxide surface, enhances the adsorption capacity of the catalyst, and improves the conductivity of the catalyst, thereby improving the electrocatalytic activity and stability of the catalyst.
[0020] 2. The present invention uses a covalent organic framework material (COF) as the shell of the catalyst. Since COF is a porous material, it will not inhibit the effective contact between the reaction substrate and CeO2 when the Ru / CeO2@COF catalyst is used, which helps to further improve the electrocatalytic activity of the catalyst.
[0021] 3. The present invention not only increases the specific surface area of the catalyst by coating the surface of spherical cerium oxide with a porous COF shell layer, but also helps to improve the uniformity of the elemental Ru nanoparticles loaded thereon, thereby further improving the conductivity of the catalyst and improving the catalytic efficiency of the catalyst.
[0022] 4. The present invention can adjust the shell thickness, shell type, and type and loading amount of the core-shell structure Ru / CeO2@COF catalyst by controlling the raw materials, process and reaction conditions of the condensation reaction conditions and the surface reduction reaction, thereby preparing catalysts with different catalytic activities to meet the needs of hydrogen evolution reaction in water electrolysis in different occasions.
[0023] 5. The surface active substances of the core-shell structured Ru / CeO2@COF catalyst prepared by the present invention are uniform in size, evenly distributed, and free of agglomeration, and have strong catalytic activity and electrochemical stability for electrocatalytic HER reaction.
[0024] 6. The core-shell structured Ru / CeO2@COF catalyst prepared by the present invention has strong catalytic activity, is suitable for catalyzing the electrolysis of water for hydrogen evolution reaction, and has a simple preparation process, easy operation, and easy mass production. It can prepare a variety of high-performance core-shell structured catalysts and has significant advantages in the fields of energy storage and the like.
[0025] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1TEM images of the core-shell structured Ru / CeO2@COF catalysts prepared in Examples 1 to 4 of the present invention.
[0027] Figure 2 This is a comparison chart of the electrocatalytic hydrogen evolution performance of the core-shell structured Ru / CeO2@COF catalysts prepared in Examples 1 to 4 of the present invention.
[0028] Figure 3 TEM images of the core-shell CeO2@COF carrier materials prepared in Examples 1 and 5-7 of the present invention. DETAILED DESCRIPTION
[0029] Example 1
[0030] This embodiment includes the following steps:
[0031] Step 1: Spherical CeO2 particles with a size of 200nm to 300nm are dispersed in water at a concentration of 20mg / mL by ultrasonic for 1h, and then 1mL of a 100mg / mL polyethyleneimine PEI aqueous solution is slowly added and stirred at room temperature for 2h. After centrifugation and washing, PEI surface-treated CeO2 nanoparticles are obtained;
[0032] Step 2: Add 100 mg of the PEI surface-treated CeO2 nanoparticles obtained in step 1 to 150 mL of anhydrous acetonitrile containing 400 mg of PVP and ultrasonically disperse for 2 h, then add 40 mg of 2,5-dimethoxybenzene-1,4-dicarboxaldehyde DMTP and 48 mg of 1,3,5-tris(4-aminophenyl)benzene TAPB and stir for 20 min, then add 2 mL of glacial acetic acid and react at room temperature for 6 h, then add 8 mL of glacial acetic acid and heat to 80 ° C to react for 12 h, and then centrifuge and wash to obtain a core-shell CeO2@COF carrier material;
[0033] Step 3: dissolve 0.0041 g of RuCl3 in 0.2 mL of methanol, and weigh 200 mg of the core-shell CeO2@COF carrier material obtained in step 2 and dissolve it in methanol to prepare a 0.1 mol / L methanol solution, then slowly drop the RuCl3 methanol solution and perform ultrasonic dispersion treatment for 1 hour, then slowly drop 3.28 mL of 0.1 mol / L sodium borohydride aqueous solution for reduction, repeatedly wash, centrifuge and dry to obtain a core-shell structure Ru / CeO2@COF catalyst; the loading amount of Ru in the core-shell structure Ru / CeO2@COF catalyst is 1% by mass.
[0034] Example 2
[0035] The difference between this embodiment and embodiment 1 is as follows:
[0036] Step 3: dissolve 0.0108 g of RuCl3 in 0.52 mL of methanol, and weigh 100 mg of the core-shell CeO2@COF carrier material obtained in step 2 and dissolve it in methanol to prepare a 0.1 mol / L methanol solution, then slowly drop the RuCl3 methanol solution and perform ultrasonic dispersion treatment for 1 hour, then slowly drop 8.54 mL of 0.1 mol / L sodium borohydride aqueous solution for reduction, repeatedly wash, centrifuge and dry to obtain a core-shell structure Ru / CeO2@COF catalyst; the Ru loading amount in the core-shell structure Ru / CeO2@COF catalyst is 5% by mass.
[0037] Example 3
[0038] The difference between this embodiment and embodiment 1 is as follows:
[0039] Step 3: dissolve 0.0228 g of RuCl3 in 1.00 mL of methanol, and weigh 100 mg of the core-shell CeO2@COF carrier material obtained in step 2 and dissolve it in methanol to prepare a 0.1 mol / L methanol solution, then slowly drop the RuCl3 methanol solution and perform ultrasonic dispersion treatment for 1 hour, then slowly drop 18.07 mL of 0.1 mol / L sodium borohydride aqueous solution for reduction, repeatedly wash, centrifuge and dry to obtain a core-shell structure Ru / CeO2@COF catalyst; the Ru loading amount in the core-shell structure Ru / CeO2@COF catalyst is 10% by mass.
[0040] Example 4
[0041] The difference between this embodiment and embodiment 1 is as follows:
[0042] Step 3: dissolve 0.0512 g of RuCl3 in 0.52 mL of methanol, and weigh 100 mg of the core-shell CeO2@COF carrier material obtained in step 2 and dissolve it in methanol to prepare a 0.1 mol / L methanol solution, then slowly drop the RuCl3 methanol solution and perform ultrasonic dispersion treatment for 1 hour, then slowly drop 40 mL of 0.1 mol / L sodium borohydride aqueous solution for reduction, repeatedly wash, centrifuge and dry to obtain a core-shell structure Ru / CeO2@COF catalyst; the Ru loading amount in the core-shell structure Ru / CeO2@COF catalyst is 20% by mass.
[0043] Figure 1TEM images of the core-shell structured Ru / CeO2@COF catalysts prepared in Examples 1 to 4 of the present invention, Figures (a) to (d) correspond to the core-shell structured Ru / CeO2@COF catalysts in Examples 1 to 4 with Ru loadings of 1%, 5%, 10%, and 20%, respectively, and the red box in the upper left corner of each figure is a partial enlarged view. Figure 1 Yes, the Ru element is evenly distributed on the surface of the outer shell of the catalyst, and the dispersion is relatively uniform. The Ru element is in granular form on the surface of the carrier without obvious agglomeration, and the particle size is about 5nm to 10nm.
[0044] The core-shell structured Ru / CeO2@COF catalysts prepared in Examples 1 to 4 of the present invention were subjected to electrocatalytic hydrogen evolution performance testing, and the specific process was as follows: first, 4 mg of catalyst powder was weighed, mixed with 2 mg of conductive carbon and a small amount of ethanol, a binder and water were added, and ultrasonicated for 30 min, then coated on a rotating disk electrode, placed under a purple light and irradiated until dry, and then the electrochemical hydrogen evolution performance was tested in a 0.1M KOH solution.
[0045] Figure 2 The electrocatalytic hydrogen evolution performance comparison diagram of the core-shell structure Ru / CeO2@COF catalysts prepared in Examples 1 to 4 of the present invention is shown in FIG. Figure 2 It can be seen that compared with CeO2 and core-shell CeO2@COF carrier materials, the core-shell structured Ru / CeO2@COF catalysts prepared in each embodiment showed a strong ability to catalyze the electrolysis of water and hydrogen evolution reaction, and its catalytic activity increased with the increase of Ru loading.
[0046] Example 5
[0047] The difference between this embodiment and embodiment 1 is as follows:
[0048] Step 1: Spherical CeO2 particles with a size of 200nm to 300nm are dispersed in water at a concentration of 10mg / mL by ultrasonic for 1h, and then 1mL of 40mg / mL polyethyleneimine PEI aqueous solution is slowly added and stirred at room temperature for 1h. After centrifugation and washing, PEI surface-treated CeO2 nanoparticles are obtained.
[0049] Example 6
[0050] The difference between this embodiment and embodiment 1 is as follows:
[0051] Step 1: Spherical CeO2 particles with a size of 200nm to 300nm are dispersed in water at a concentration of 40mg / mL by ultrasonic for 1h, and then 1mL of 200mg / mL polyethyleneimine PEI aqueous solution is slowly added and stirred at room temperature for 1h. After centrifugation and washing, PEI surface-treated CeO2 nanoparticles are obtained.
[0052] Example 7
[0053] This embodiment includes the following steps:
[0054] Step 1: Spherical CeO2 particles with a size of 200nm to 300nm are dispersed in water at a concentration of 20mg / mL by ultrasonic for 1h, and then 1mL of a 100mg / mL polyethyleneimine PEI aqueous solution is slowly added and stirred at room temperature for 1h. After centrifugation and washing, PEI surface-treated CeO2 nanoparticles are obtained;
[0055] Step 2: 100 mg of the PEI surface-treated CeO2 nanoparticles obtained in step 1 was added to 150 mL of anhydrous acetonitrile containing 400 mg of PVP and ultrasonically dispersed for 0.5 h, and then 60 mg of 2,5-dimethoxybenzene-1,4-dicarboxaldehyde DMTP and 72 mg of 1,3,5-tris(4-aminophenyl)benzene TAPB were added and stirred for 5 min, followed by adding 2 mL of glacial acetic acid and reacting at room temperature for 4 h, and then adding 8 mL of glacial acetic acid and heating to 80 ° C to react for 12 h, and then centrifuging and washing to obtain a core-shell CeO2@COF carrier material;
[0056] Step 3: dissolve 0.0041 g of RuCl3 in 0.2 mL of methanol, and weigh 200 mg of the core-shell CeO2@COF carrier material obtained in step 2 and dissolve it in methanol to prepare a 0.1 mol / L methanol solution, then slowly drop the RuCl3 methanol solution and perform ultrasonic dispersion treatment for 1 hour, then slowly drop 3.28 mL of 0.1 mol / L sodium borohydride aqueous solution for reduction, repeatedly wash, centrifuge and dry to obtain a core-shell structure Ru / CeO2@COF catalyst; the loading amount of Ru in the core-shell structure Ru / CeO2@COF catalyst is 1% by mass.
[0057] Example 8
[0058] This embodiment includes the following steps:
[0059] Step 1: Spherical CeO2 particles with a size of 200nm to 300nm are dispersed in water at a concentration of 20mg / mL by ultrasonic for 1h, and then 1mL of a 100mg / mL polyethyleneimine PEI aqueous solution is slowly added and stirred at room temperature for 1h. After centrifugation and washing, PEI surface-treated CeO2 nanoparticles are obtained;
[0060] Step 2: 100 mg of the PEI surface-treated CeO2 nanoparticles obtained in step 1 was added to 150 mL of anhydrous acetonitrile containing 400 mg of PVP and ultrasonically dispersed for 0.5 h, then 80 mg of 2,5-dimethoxybenzene-1,4-dicarboxaldehyde DMTP and 96 mg of 1,3,5-tris(4-aminophenyl)benzene TAPB were added and stirred for 5 min, followed by adding 2 mL of glacial acetic acid and reacting at room temperature for 4 h, then adding 8 mL of glacial acetic acid and heating to 80 ° C to react for 12 h, and then centrifuging and washing to obtain a core-shell CeO2@COF carrier material;
[0061] Step 3: dissolve 0.0041 g of RuCl3 in 0.2 mL of methanol, and weigh 200 mg of the core-shell CeO2@COF carrier material obtained in step 2 and dissolve it in methanol to prepare a 0.1 mol / L methanol solution, then slowly drop the RuCl3 methanol solution and perform ultrasonic dispersion treatment for 1 hour, then slowly drop 3.28 mL of 0.1 mol / L sodium borohydride aqueous solution for reduction, repeatedly wash, centrifuge and dry to obtain a core-shell structure Ru / CeO2@COF catalyst; the loading amount of Ru in the core-shell structure Ru / CeO2@COF catalyst is 1% by mass.
[0062] Example 9
[0063] This embodiment includes the following steps:
[0064] Step 1: Spherical CeO2 particles with a size of 200nm to 300nm are dispersed in water at a concentration of 20mg / mL by ultrasonic for 1h, and then 1mL of a 100mg / mL polyethyleneimine PEI aqueous solution is slowly added and stirred at room temperature for 1h. After centrifugation and washing, PEI surface-treated CeO2 nanoparticles are obtained;
[0065] Step 2: Add 100 mg of the PEI surface-treated CeO2 nanoparticles obtained in step 1 to 150 mL of anhydrous acetonitrile containing 400 mg of PVP and ultrasonically disperse for 0.5 h, then add 120 mg of 2,5-dimethoxybenzene-1,4-dicarboxaldehyde DMTP and 144 mg of 1,3,5-tris(4-aminophenyl)benzene TAPB and stir for 5 min, then add 2 mL of glacial acetic acid and react at room temperature for 4 h, then add 8 mL of glacial acetic acid and heat to 80 ° C to react for 12 h, and obtain a core-shell CeO2@COF carrier material after centrifugation and washing;
[0066] Step 3: dissolve 0.0041 g of RuCl3 in 0.2 mL of methanol, and weigh 200 mg of the core-shell CeO2@COF carrier material obtained in step 2 and dissolve it in methanol to prepare a 0.1 mol / L methanol solution, then slowly drop the RuCl3 methanol solution and perform ultrasonic dispersion treatment for 1 hour, then slowly drop 3.28 mL of 0.1 mol / L sodium borohydride aqueous solution for reduction, repeatedly wash, centrifuge and dry to obtain a core-shell structure Ru / CeO2@COF catalyst; the loading amount of Ru in the core-shell structure Ru / CeO2@COF catalyst is 1% by mass.
[0067] Figure 3 TEM images of the core-shell CeO2@COF carrier materials prepared in Examples 1 and 7 to 9 of the present invention, wherein Figures (a) to (d) correspond to the core-shell CeO2@COF carrier materials prepared in Examples 1 and 7 to 9, respectively, and Figures (a1) to (d1) are enlarged views of Figures (a) to (d), respectively. Figure 3 It can be seen that the COF shell layer in the core-shell CeO2@COF carrier material prepared in each embodiment tightly covers the CeO2 particles, and as the dosage of the COF precursor increases, the COF shell layer becomes thicker significantly.
[0068] Example 10
[0069] This embodiment includes the following steps:
[0070] Step 1: Spherical CeO2 particles with a size of 200nm to 300nm are dispersed in water at a concentration of 20mg / mL by ultrasonic for 1h, and then 1mL of a 100mg / mL polyethyleneimine PEI aqueous solution is slowly added and stirred at room temperature for 1h. After centrifugation and washing, PEI surface-treated CeO2 nanoparticles are obtained;
[0071] Step 2: Add 100 mg of the PEI surface-treated CeO2 nanoparticles obtained in step 1 to 150 mL of anhydrous acetonitrile containing 400 mg of PVP and ultrasonically disperse for 0.5 h, then add 240 mg of terephthalaldehyde TPA and 288 mg of metaphenylenediamine MPA and stir for 5 min, then add 2 mL of glacial acetic acid and react at room temperature for 4 h, then add 8 mL of glacial acetic acid and heat to 80 ° C to react for 12 h, and then centrifuge and wash to obtain a core-shell CeO2@COF carrier material;
[0072] Step 3: dissolve 0.0041 g of RuCl3 in 0.2 mL of methanol, and weigh 200 mg of the core-shell CeO2@COF carrier material obtained in step 2 and dissolve it in methanol to prepare a 0.1 mol / L methanol solution, then slowly drop the RuCl3 methanol solution and perform ultrasonic dispersion treatment for 1 hour, then slowly drop 3.28 mL of 0.1 mol / L sodium borohydride aqueous solution for reduction, repeatedly wash, centrifuge and dry to obtain a core-shell structure Ru / CeO2@COF catalyst; the loading amount of Ru in the core-shell structure Ru / CeO2@COF catalyst is 1% by mass.
[0073] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing a core-shell structure Ru / CeO2@COF catalyst, characterized in that: The method comprises the following steps: Step 1, ultrasonically dispersing spherical CeO2 particles in water, then slowly adding polyethyleneimine PEI aqueous solution and stirring at room temperature, and centrifugally washing to obtain PEI surface-treated CeO2 nanoparticles; Step 2: Add the PEI surface-treated CeO2 nanoparticles obtained in step 1 to anhydrous acetonitrile containing PVP for ultrasonic dispersion, then add 2,5-dimethoxybenzene-1,4-dicarboxaldehyde DMTP and 1,3,5-tris(4-aminophenyl)benzene TAPB and stir, then add glacial acetic acid to react at room temperature, then add glacial acetic acid to heat and react, and obtain a core-shell CeO2@COF carrier material after centrifugation and washing; Step 3: dissolve RuCl3 in methanol to prepare RuCl3 methanol solution, disperse the core-shell CeO2@COF carrier material obtained in step 2 in the methanol solution, then slowly drop the RuCl3 methanol solution and perform ultrasonic dispersion treatment, then slowly drop sodium borohydride aqueous solution for reduction, repeatedly wash, centrifuge and dry to obtain a core-shell structured Ru / CeO2@COF catalyst.
2. The method for preparing a core-shell structured Ru / CeO2@COF catalyst according to claim 1, characterized in that: The size of the spherical CeO2 particles in step 1 is 200nm to 300nm.
3. The method for preparing a core-shell structure Ru / CeO2@COF catalyst according to claim 1, characterized in that: The concentration of the spherical CeO2 particles ultrasonically dispersed in water in step 1 is 10 mg / mL to 40 mg / mL, the concentration of the polyethyleneimine PEI aqueous solution is 50 mg / mL to 200 mg / mL, and the mass ratio of polyethyleneimine PEI to spherical CeO2 particles is 3:1 to 6:
1.
4. The method for preparing a core-shell structured Ru / CeO2@COF catalyst according to claim 1, characterized in that: The ultrasonic dispersion time in step 1 is 1 hour, and the stirring time at room temperature is 1 hour to 2 hours; the ultrasonic dispersion time in step 2 is 0.5 hours to 2 hours; and the ultrasonic treatment time in step 3 is 1 hour to 2 hours.
5. The method for preparing a core-shell structure Ru / CeO2@COF catalyst according to claim 1, characterized in that: In step 2, the mass ratio of DMTP to TAPB is 40-120:48-144, and the stirring time is 5 min to 20 min.
6. The method for preparing a core-shell structured Ru / CeO2@COF catalyst according to claim 1, characterized in that: The reaction time at room temperature in step 2 is 4 to 6 hours, and the heating reaction temperature is 80° C. for 12 hours.
7. The method for preparing a core-shell structured Ru / CeO2@COF catalyst according to claim 1, characterized in that: The 2,5-dimethoxybenzene-1,4-dicarboxaldehyde DMTP and 1,3,5-tris(4-aminophenyl)benzene TAPB described in step 2 can also be replaced by meta-phenylenediamine MPA and terephthalaldehyde TPA in a mass ratio of 60-240:72-244.
8. The method for preparing a core-shell structured Ru / CeO2@COF catalyst according to claim 1, characterized in that: The loading amount of Ru in the core-shell structured Ru / CeO2@COF catalyst in step 3 is 1% to 20% by mass.
9. Use of a core-shell structured Ru / CeO2@COF catalyst prepared by the method according to any one of claims 1 to 8 in a hydrogen evolution reaction by electrolysis of water.
Citation Information
Patent Citations
CeO2 micro-flower loaded Ru nano-particle compound and preparation method thereof
CN114425334A
COF-based catalyst with core-shell structure as well as preparation method and application of COF-based catalyst
CN117483009A
Non-noble metal two-component dehydrogenation catalyst as well as preparation method and application thereof
CN118807848A
Metallic nano-catalyst having semi-coated structure, preparation method therefor and application thereof
WO2023077609A1